(R)-WAC-224, a new anticancer quinolone, combined with venetoclax and azacitidine overcomes venetoclax-resistant AML through MCL-1 downregulation - Hiroshi Ureshino; Taichi Ueshima; Tomonori Yamaguchi; Miyuki Takashima; Yusuke Sanuki; Tatsuo Ichinohe (Scientific Reports)
Abstract Hypomethylating agents combined with venetoclax (VEN), a BCL-2 inhibitor, represent a standard treatment strategy for patients with acute myeloid leukemia (AML). Although this combination is highly effective, acquired resistance commonly occurs. MCL-1, a BCL-2 family molecule, is frequently upregulated in VEN-resistant cells, playing a major role in VEN resistance. Previously, we demonstrated that (R)-WAC-224 is effective against AML with minimal cardiac toxicity. (R)-WAC-224 combined with VEN demonstrated strong antileukemia effects on VEN-resistant AML cells overexpressing MCL-1 in vitro. Gene expression profiles revealed that (R)-WAC-224 with VEN induced DNA damage pathways leading to cell apoptosis. (R)-WAC-224 elicited caspase 3 activation, which cleaved MCL-1; this effect was reversed by a caspase inhibitor, thus overcoming VEN resistance. A combination of azacitidine (AZA), a hypomethylating agent, VEN, and (R)-WAC-224 was highly effective against VEN-resistant AML in vivo without increasing toxicity. (R)-WAC-224 exhibited antileukemia effects on VEN-resistant AML via MCL-1 downregulation in vitro and in vivo. The combination of AZA, VEN, and (R)-WAC-224 may be a promising treatment strategy for patients with AML.